Atmospheric forcing intensifies the effects of regional ocean warming on reef‐scale temperature anomalies during a coral bleaching event. Issue 9 (18th September 2013) - Zhang, Zhenlin; Falter, James; Lowe, Ryan; Ivey, Greg; McCulloch, Malcolm
<x xml:space="preserve">Abstract</x> [1] We investigate how local atmospheric conditions and hydrodynamic forcing contributed to local variations in water temperature within a fringing coral reef‐lagoon system during the peak of a marine heat wave in 2010–2011 that caused mass coral bleaching across Western Australia. A three‐dimensional circulation model Regional Ocean Modeling System (ROMS) with a built‐in air‐sea heat flux exchange module Coupled Ocean Atmosphere Experiment (COARE) was coupled with a spectral wave model Simulating Waves Nearshore (SWAN) to resolve the surface heat exchange and wave‐driven reef circulation in Coral Bay, Ningaloo Reef. Using realistic oceanic and atmospheric forcing, the model predictions were in good agreement with measured time series of water temperature at various locations in the coral reef system during the bleaching event. Through a series of sensitivity analyses, we found that the difference in temperature between the reef and surrounding offshore waters (ΔT) was predominantly a function of both the daily mean net heat flux ( <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgg4t8w4bz0" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />Qnet¯</alternatives>) and residence time, whereas diurnal variations in reef water temperature were dependent on the diurnal fluctuation in the net heat flux. We found that reef temperatures were substantially higher than offshore in the inner lagoon under normal weather conditions and over the entire reef domain under more extreme weather conditions (0.7°C–1.5°C). Although these temperature elevations were still less than that caused by the regional ocean warming (2°C–3°C), the arrival of peak seasonal temperatures in the summer of 2010–2011 (when net atmospheric heat fluxes were positive and abnormally high) caused substantially higher thermal stresses than would have otherwise occurred if offshore temperatures had reached their normal seasonal maxima in autumn (when net atmospheric heat fluxes were negative or cooling). Therefore, the degree heating weeks calculated based on offshore temperature substantially underestimated the thermal stresses experienced by the reef in the period leading up to the observed bleaching event (3 versus 11°C‐weeks).